Practitioner perspectives on service users experiences of targeted violence and hostility in mental health and adult safeguarding. Issue 7 (9th August 2021) - Hafford-Letchfield, Trish; Carr, Sarah; Faulkner, Alison; Gould, Dorothy; Khisa, Christine; Cohen, Rachel; Megele, Claudia
Abstract: People with lived experience of mental distress experience high rates of targeted violence and hostility based on their mental health status. This user-led study explored practitioners' perceptions and experiences of supporting service users in these challenging situations and considered the role of adult safeguarding. Six focus groups with practitioners ( n = 46) enabled them to respond to data documenting service user's experiences. This process facilitated knowledge exchange between the research team and practitioners on the ground. The findings illuminate a complex picture where lack of effective structures and processes mitigate against service users in these difficult situations. Practitioners need to invest in trusting relationships, to optimise resources and actively help service users with lived experience of mental distress to find their own solutions. These should involve collaborative empowerment whereby feelings of isolation and rejection can be replaced with hope, a sense of agency and belief in personal control. Points of interest: People with lived experience of mental distress are at a high risk of exposure to hate crimes, hostility and discrimination. These risks and those experiencing them, often go unrecognised. There is a lack of knowledge and understanding about what people need, how they cope and what helps in these situations. Professionals and practitioners from different disciplines face very complex challenges in responding to and helping people, resulting in service users falling through the net when they need it most. Services in the community and hospital are not working together effectively to support people experiencing targeted violence and hostility. There is a lack of coherence in the way that the criminal justice system and adult safeguarding frameworks support effective working. There is an urgent need to listen to and engage with service users' own voices in these environments and to work with them to find solutions that help them feel safe and in control. These should particularly utilise relationship-based practice and peer support.